2004
DOI: 10.1152/japplphysiol.00479.2003
|View full text |Cite
|
Sign up to set email alerts
|

Viral expression of insulin-like growth factor-I enhances muscle hypertrophy in resistance-trained rats

Abstract: Muscle hypertrophy is the product of increased drive through protein synthetic pathways and the incorporation of newly divided satellite cells. Gains in muscle mass and strength can be achieved through exercise regimens that include resistance training. Increased insulin-like growth factor-I (IGF-I) can also promote hypertrophy through increased protein synthesis and satellite cell proliferation. However, it is not known whether the combined effect of IGF-I and resistance training results in an additive hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
127
1
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(145 citation statements)
references
References 37 publications
8
127
1
9
Order By: Relevance
“…RT was implemented using a ladder climbing apparatus as described by Lee et al (2004). Briefly, the device was 1 m in length at a 75° incline with 1 cm of space between adjacent ladder rails.…”
Section: Resistance Training (Rt)mentioning
confidence: 99%
See 1 more Smart Citation
“…RT was implemented using a ladder climbing apparatus as described by Lee et al (2004). Briefly, the device was 1 m in length at a 75° incline with 1 cm of space between adjacent ladder rails.…”
Section: Resistance Training (Rt)mentioning
confidence: 99%
“…10 g, 15 g, 20 g, or 40 g) to the base of the rat's tail with foam tape and a clip. The RT protocol was adapted from Lee et al (2004), who demonstrated that ladder climbing produced a 23.3% increase in muscle mass following 8 weeks of training. Daily training consisted of 8 total repetitions beginning with one repetition at 70% of maximum weight determined from pre-test (MAX), two repetitions at 80% MAX, two repetitions at 90% MAX, one repetition at MAX, one repetition at MAX plus 20 g, and one repetition at MAX plus 40 g. Two-minute rest intervals were provided between repetitions.…”
Section: Resistance Training (Rt)mentioning
confidence: 99%
“…[15][16][17] Viral-mediated IGF-I delivery prevents the age-related loss of skeletal muscle function and has been shown to promote skeletal muscle hypertrophy in an additive manner when combined with resistance exercise training. 18,19 Non-viral plasmid-based electroporationassisted IGF-I gene transfer has been shown to enhance skeletal muscle regeneration after laceration injury. 20 Administration of recombinant IGF-I protein has been shown to promote restoration of muscle function after strain or laceration injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Such episode was observed both in animals which were submitted to strength training and sedentary ones. When the extra IGF-1 gene introduction was combined with strength training, hypertrophy and strength development were higher than the ones observed in only strength-trained animals (and not super-expressed IGF-1) and in the ones which only super-expressed IGF-1 (and did not train strength) (13) . Thus, it can be said that the IGF-1 superexpression may boost in great magnitude the muscular responses to physical training, especially in strength training.…”
Section: Igf-1 and Ghmentioning
confidence: 68%
“…Since it is still in eminently experimental character stage, there are problems in the gene therapy application, being its risks control one of the most important (7)(8)(9)(10)(11) . However, studies in animal models (2,(12)(13)(14)(15) as well as some studies in humans (1,(6)(7)(16)(17)(18)(19) have presented promising results.…”
Section: Introductionmentioning
confidence: 99%